ISTEM JARINGAN INTERNET DATA UNTUK PENDISTRIBUSIAN VLAN - Peniarsih Peniarsih (JURNAL MITRA MANAJEMEN, 2014)
ABSTRACTWith Internet technology capable bekomunikasi someone , send and process data without limit and timethough. If the current telnologi lot of circulation data and will possibly involve many agencies orcompanies or even be terjalain cooperation of various companies in the data traffic activity. This is wherethe role of a company's internet service provider or ISP ( internet sevice provider) is required , with thepresence of an internet service provider company will help companies to improve the performance of thecompany due to savings in time and costs with the reliability of the information and data obtainedkeakurantan.Internet service provider (ISP) there are a wide variety of network topologies, the concept of VLAN(Virtual Local Area Network), a hard ware components and uses the IP address that is used fordistribution of internet services to companies (cutomer) Perform analysis of network systems/networkingthere VLAN using the distribution (Virtual Area Network) and the concept of VLAN (Virtual Local AreaNetwork). And Providing solutions to the problems of network systems .